Генотоксическое влияние фтора питьевой воды - Верголяс, М.Р.; Головков, А.Н.; Наниева, А.В.; Пелишенко, А.В.; Гончарук, В.В. (Фактори експериментальної еволюції організмів, 2016)
Aim. Fluoride is widely distributed in nature and contains in minerals, ores, soils, atmosphere, natural waters, plant and animal organisms. One measure of the quality of drinking water is its content of fluorine. Getting in an organism of animals and humans, fluoride reacts with iron, manganese, nickel and other chemical elements to form complex compounds that inhibit the action of enzymes and disrupt the metabolism. Methods. In this paper we studied the effect of different concentrations of fluoride ions in the blood cells of the test organism (fish, Danio rerio), because for Ukraine content of fluoride ions in the subterranean sources of drinking water supply varies in a fairly wide range. The national average, the figure is 2.5–12 mg/dm³. Results. During the bioassay using fish Danіo rerіo acute toxicity was not observed, the survival rate of the test organisms in all concentrations was 100%. The water samples at concentrations of 1.5 mg/dm³ and 3.0 mg/dm³ and the number of micronuclei twins reached values of 0.99 ‰ and 1.65 ‰, respectively, indicating manifestation genotoxic effect. Conclusions. A water sample with fluoride ion concentration of 1.0 mg/dm³ did not show genotoxic effect and meets WHO requirements. Fluoride is an essential component for the normal functioning of the body and of animals and humans, its surplus or deficiency can lead to serious negative consequences.